2020
DOI: 10.3390/molecules25235622
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Tangeretin by Inhibiting PTEN/AKT/mTOR Axis in Experimental Sepsis-Induced Myocardial Dysfunction

Abstract: Sepsis aggregates undesirable immune response causing depression of ventricular myocardium and diastolic dysfunction. This present study examined the effect of a plant-derived flavone tangeretin (TG) on autophagy and reduction in myocardial dysfunction. The sepsis was induced by cecum ligation and puncture (CLP) in male Sprague–Dawley rats. Abnormal changes were seen in the heart after the sepsis induction. These abnormalities were analyzed based on the cardiac markers, namely Cardiac myosin light chain-1 (cML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Moreover, overexpression of AKT decreased the autophagy activity mediated by acetylated TAN. TAN also attenuated myocardial dysfunction acting on the AKT/mTOR pathway . In this study, in the BIIC group, both the decreased level of soluble p62 and the increased ratio of LC3 II to LC3 I indicated the activation and increment of autophagy degree. , Comparing with the BIIC stimulated group, the phosphorylation level of Akt and mTOR was significantly increased with the treatment of TAN or 5-HPMF, demonstrating that TAN and 5-HPMF alleviated the autophagy level through the Akt signaling pathway, which is consistent with the results from TEM examination.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, overexpression of AKT decreased the autophagy activity mediated by acetylated TAN. TAN also attenuated myocardial dysfunction acting on the AKT/mTOR pathway . In this study, in the BIIC group, both the decreased level of soluble p62 and the increased ratio of LC3 II to LC3 I indicated the activation and increment of autophagy degree. , Comparing with the BIIC stimulated group, the phosphorylation level of Akt and mTOR was significantly increased with the treatment of TAN or 5-HPMF, demonstrating that TAN and 5-HPMF alleviated the autophagy level through the Akt signaling pathway, which is consistent with the results from TEM examination.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the present study can be compared to the neuroprotective signaling cascades enumerated against Alzheimer's disease and Parkinsonism through a comprehensive review [28]. Cardioprotectiveness of tangeretin was a rmed for the interplay between PTEN/AKT/mTOR pathways in vivo [29]. The putative targets obtained from the study will have pivotal signi cance in the future for microglial activation strategy and blood brain barrier compatibility.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence has shown that dysregulation of mTOR signalling is linked to many human diseases, including diabetes, neurodegenerative diseases, and cancer 26 . A previous study successfully showed that TG attenuates sepsis‐induced myocardial dysfunction by inhibiting myocardial autophagy by silencing PTEN expression and acting on the AKT/mTOR pathway 27 . Based on the function of the DPPs and their associated signalling pathways, we selected Rps6, Ywhag, Pten, Pkn2, Magi1, and mTOR, which participate in the PI3K‐Akt signalling pathway, for verification.…”
Section: Discussionmentioning
confidence: 99%
“… 26 A previous study successfully showed that TG attenuates sepsis‐induced myocardial dysfunction by inhibiting myocardial autophagy by silencing PTEN expression and acting on the AKT/mTOR pathway. 27 Based on the function of the DPPs and their associated signalling pathways, we selected Rps6, Ywhag, Pten, Pkn2, Magi1, and mTOR, which participate in the PI3K‐Akt signalling pathway, for verification. The total protein levels of Rps6, Ywhag, Pten, Pkn2, Magi1, and mTOR were not changed, but the phosphorylation levels of these proteins were increased.…”
Section: Discussionmentioning
confidence: 99%